Structural aspects of shrubs in Mediterranean-type plant communities - Kummerow J. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The purpose of this contribution is to discuss the adaptive value of a few morphological characteristics of shrubs of Mediterranean-type ecosystems. Structural characters, such as the crypts in the leaf epidermis of some sclerophyllous shrub species, the smooth bark of many chaparral shrubs, which increases stem flow and thus adds water and fertiliser to the root crown area which is specially high in fine-root density, or the presence of vasicentric tracheids in the wood of drought supporting shrubs, seem ideally 'designed' to improve shrub response to drought conditions. However, experimental evidence for the adaptive value of these structures is widely missing. The phenomorphological analysis of the plants of Mediterranean-type ecosystems has the potential to improve the objectivity of scrub vegetation comparisons and to elucidate the adaptive value of these structural features. Overall, it is concludes that suites of anatomical features and not single characters decide upon the adaptive value of morphological properties.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)